Internet Usage For Learning Interest In UNISRI Surakarta In 2018 - Yusuf Yusuf (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The development of computer technology and telecommunications so fast thatpervasive in everyday human life. In the 21st century, computers become a veryconventional media in the world, especially with other technologies that have beenembedded in it is the internet network. The Internet network is a computer networkcapable of connecting computers around the world, so information in differenttypes and in various forms can be communicated between the world in an instantand globally. Information technology has opened the eyes of the world to a newworld, new interactions, a new market place, and an unlimited world businessnetwork. To that end, the purpose of this study is to determine the use of theInternet as a source of learning from students Slamet Riyadi University Surakarta.This research is designed with qualitative discriptip research approach. Internetprovided by Unisri with bandwidth 40 MBPS with rental value Rp. 15,000,000 permonth. In fact, ideally Unisri with students about 4000 an and to support theperformance of lecturers and employees, the Unisri requires Bandwidth 100 to 200MBPS. The limited bandwidth conditions in use are distributed to the Faculty ofLaw with 2 MBPS and a maximum of 4 MBPS. Faculty of Economics with 3MBPS and maximum 5 MBPS. Fisipol with 2 MBPS and maximum 4 MBPS.FKIP with 3 MBPS and maximum 5 MBPS. Faculty of Agriculture with 2 MBPSand maximum 4 MBPS. Fatipa with 3 and maximum 5 MBPS. Post with 2 MBPSwith maximum 4 MBPS. Library with 8 MBPS and maximum 10 MBPS.University Office with 5 MBPS and maximum 8 MBPS. Seeing the distribution ofinternet network Unisri for Faculty of Economics, Faculty of Law, Fisipol, Fatipa,faculty of agriculture, internet usage to support the learning process, students canbe used relatively, though students still often use HP Androidnya because Unisriinternet network perceived student very slow. Special students FKIP is stilldifficult to access the internet Unisri in class when the learning process takes place.Unlimited Bandwidth Limitations FKIP proposes to raise Banwith internet Unisri,but no follow-up. As a result, FKIP Unisri installed its own internet with a capacityof 100 MBPS for the benefit of lecturers and administrative support of education,but not accessible to students, with the amount of rent Rp. 1.6 million rupiah eachmonth. The fact that the use of the Internet for the benefit of learning despitealready implemented, but not maximal due to lecturer factors that do notmaximally use the internet in learning and in the assignment, because of the slowinternet and less familiar lecturer to the internet. On the student side become moreuse internet more as entertainment media.